New method to estimate bedrock shape of small-scale basin using modal properties of sediment. Issue 149 (October 2021) - Suzuki, Yusuke; Iiyama, Kahori; Morikawa, Hitoshi; Sakai, Kimitoshi; Araki, Go
Abstract: 2-D resonances are known to occur in sedimentary basins, and it has been reported that the fundamental mode shapes appear to reflect the bedrock shape. This suggests that the bedrock shape of a valley can be estimated by evaluating the relationship between the mode shapes and the bedrock shape, and by identifying the resonance modes from the observation records of the ground motions. In the present study, the fundamental mode shapes of a small-scale valley were identified by applying the frequency domain decomposition (FDD) technique to microtremor observation records. 2-D finite difference models were used to investigate the relationship between the mode shapes and the bedrock shape. A new method was proposed for estimating the bedrock shape by comparing the mode shapes obtained from observation records and a numerical analysis. Furthermore, the applicability of the new method was confirmed using synthetic and observed data.